New(spaper) Evidence of a Reduction in Suicide Mentions during the 19th-century US Gold Rush - Christoph Kronenberg (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2020)
I analyze the relationship between state-level economic shocks and suicides using historical US gold discoveries (1840-1860) as a large unexpected economic shock. Gold discoveries were an unexpected and large economic shock of up to 3.5% of GDP. They provide as good as random variation to the local economy, that I use to estimate the effect of economic changes on suicides. Comprehensive mortality data by state and year does not exist for the US for 1840 to 1860. I thus make use of web scraped data from a newspaper archive and use suicide mentions per 100,000 pages as a proxy for suicides. Results show that overall gold discoveries are linked with a clear reduction in newspaper suicide mentions. The results indicate that an economic shock changes the suicide rate by one for every 136,659 to 251,145. This is estimate implies a higher cost-effectiveness than previous research but is still seven to fourteen times the size of modern, cost-effective suicide prevention method.
Keywords: N31; I15; J11; 330; Gold Rush; Economic Shock; Suicide; Newspaper